(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2023)
The aim of this paper is the production and characterization of biodiesel from Moringa stenopetala seed oil. Biodiesel is a renewable, biodegradable, and nontoxic biofuel. Moringa stenopetala seed oil is a potential feedstock that has not been discovered as an energy source. This study investigated the effects of process parameters: methanol to oil ratio, reaction temperature, and catalyst loading on the yield and quality of biodiesel. The experimental results showed that the maximum biodiesel yield was 94% and it was obtained at optimum process conditions: temperature 55°C, methanol to oil ratio 6:1, and catalyst loading1.0. Biodiesel product was characterized based on international standards for testing fuels. According to the findings of the study, moringa stenopetala seed oil biodiesel has a specific gravity of 0.874 g/mole, a kinematic viscosity of 4.8 mm2/s, an acid value of 0.4 mg KOH/g, a saponification value of 196 mg KOH/g, FFA 0.2%, iodine value 104.5 high heating value 10,287 cal/g, flash Point 184°C, pour point 1°C, cloud point 10°C and cetane number 53. These results satisfy international standards for biodiesel. Bangladesh J. Sci. Ind. Res. 58(1), 35-44, 2023